2017
DOI: 10.5897/sre2017.6516
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of 3.60 m3 household plastic bio digester loaded with kitchen waste and cow dung for biogas generation

Abstract: A 3.6 m 3 pilot plastic digester for family generation of biogas was designed, constructed and evaluated through physico-chemical studies using 50% cow dung and 50% kitchen wastes. The ash content of waste increased after digestion while the fibre and fat contents of the waste was 5.10 and 1.05% but significantly (p<0.05) decreased to 2.49 and 0.70% after digestion. The carbohydrate content of the waste was 11.02% which significantly (p<0.05) decreased to 7.91%. The volatile solid content of 50% cow dung + 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 13 publications
5
14
0
1
Order By: Relevance
“…The mesophilic (21˚C -38˚C) is the temperature range that was identified from the slurry temperature. This is similar to the result observed by Otun et al [7] and Nwanko et al [11]. From the results obtained, anaerobic bacteria thrive best at a mesophilic temperature of about 34˚C [27] [40].…”
Section: Effects Of Temperature and Phsupporting
confidence: 90%
See 4 more Smart Citations
“…The mesophilic (21˚C -38˚C) is the temperature range that was identified from the slurry temperature. This is similar to the result observed by Otun et al [7] and Nwanko et al [11]. From the results obtained, anaerobic bacteria thrive best at a mesophilic temperature of about 34˚C [27] [40].…”
Section: Effects Of Temperature and Phsupporting
confidence: 90%
“…It was also observed that the changes in the pH value also resulted in changes in the volume of gas produced, as consistency in the higher range of pH favours the methanogenic bacteria. These bacteria are inhibited in pH greater than 8 or less than 5 as reported by Nwanko et al [11] and Okewale [40]. Figure 2 shows the slurry temperature trend of the mixed substrates.…”
Section: Effects Of Temperature and Phsupporting
confidence: 56%
See 3 more Smart Citations